Geopolitical shockwaves: the Russia-Ukraine war’s impact on BRICS financial markets - Suresh Gopal; Viswanathan Thangaraj; Naveen Kumara R.; Rupa R. (Cogent Economics & Finance)
The Russia-Ukraine War triggered global financial market turmoil and disrupted the global supply chain, including agriculture and energy. This study explores the impact of the Russia-Ukraine war on BRICS nations’ stock markets, highlighting varying degrees of volatility and contagion effects. It examines the extent of contagion in the BRICS stock markets and their financial linkages by employing the multivariate DCC-GARCH model. The study reveals sensitive turbulence in Russian markets post-crisis, influenced by its direct involvement in the conflict. Brazil and China experienced higher market volatility after the event, and Brazil shifted its financial linkages with the global market. Conversely, the Indian market experienced eased overall volatility, but its financial linkage with Russia has increased due to its trade partnership. In the post-event period, China and South African markets indicate structural market decoupling. The long-term volatility persists over the short-term volatility of BRICS market dynamics. This study underscores the implications for investors and policymakers, emphasising the need for adjustments in monetary and fiscal policies to stabilise financial markets amid geopolitical uncertainties.